Intermedial Modernism: Mina Loy, E. E. Cummings, and Poet-Painter Artisthood - Wang, Bowen (Trinity College Dublin. School of English. Discipline of English, 2024)
This study focuses on the figure of modernist poet-painters, specifically Mina Loy and E. E. Cummings, within a redefined context of intermedial modernism in the early twentieth century. Through an in-depth exploration of their verbal-visual artistries, it examines the dialectical dynamics and collaborative nature of intermediality as the substrate to reformulate the formalist or materialist aesthetics of modernism. Both Loy and Cummings were adept in modernist poetries and artworks, actively engaging in a wide range of avant-garde art movements such as Italian Futurism, New York Dada, Fauvism and Cubism in Paris. Their transcontinental exchanges across the Atlantic and the Pacific provide valuable insights into the fluid, transformative agency of their dual identities. Furthermore, this dissertation explores how the poetics of intermedial artisthood realigns typeset words and phrases with spatial layout and construction. Loy's manifestic designs, verbal readymades, painterly abstractions and Cummings' gestural line-drawings, vital still lifes, landscapes, are extensively investigated to showcase a captivating series of modernist re-presentations of word, image, object and identity. In defying the preordained boundaries and hierarchies between the sayable and the seeable, they shed light on the alternative medialities or modalities in a broad narrative for us to experience and reimagine the tangible world. Loy's cosmopolitan avant-gardism and intermedial portraiture, along with Cummings' intercultural influences and intermedial prosody, demonstrate the profound creativity achieved through this image-text convergence which is integral to a medium-specific modernist aesthetics and the reconfiguration of artistic and social spaces in that historical epoch. As such, the dissertation delves into their bold experimentation, illuminating the significance of intermediality in the modernist refashioning of style, form, and material. The separate realms of reading and spectatorship are bridged with cultural, technological, and ideological implications. In contrast to traditional textual criticism, this study highlights an intermedial reading that brings Loy's and Cummings' art practices, including not only paintings or drawings in various materials but also designs as objet d'art, illustrations, collages, murals, and sketches with written notes, into close consideration. It thus sets the stage for new crossroads of modernist studies and intermedial studies, and poses important questions about the nature of discourse and expression, the interplay between text and vision, the transgression of artistic disciplines, and the potential prism of intermediality to challenge and reshape our linearist or literalist conception of language and art.
APPROVED
Keywords: Intermediality; Mina Loy; E. E. Cummings; Poet-Painter; Modernism